2016
DOI: 10.12973/eurasia.2017.00639a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Prospective Teachers’ Mathematical Modeling Processes in the Context of a Mathematical Modeling Course

Abstract: This paper investigates how prospective teachers develop mathematical models while they engage in modeling tasks. The study was conducted in an undergraduate elective course aiming to improve prospective teachers' mathematical modeling abilities, while enhancing their pedagogical knowledge for the integrating of modeling tasks into their future classroom practices. The participants of this study were six prospective teachers selected among the nineteen who enrolled in the course. Data was collected through fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
11
0
5
Order By: Relevance
“…This difference was found to be in favour of post-test scores and showed similar results with the research of Zeytun et al (2017). According to this, it is concluded that the mathematical modelling method is more effective than the 5E Instructional Model, although it is seen that the students in the Experiment group 2 in which the mathematical modelling method is applied are more successful in the post-test when the post-test scores are examined.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This difference was found to be in favour of post-test scores and showed similar results with the research of Zeytun et al (2017). According to this, it is concluded that the mathematical modelling method is more effective than the 5E Instructional Model, although it is seen that the students in the Experiment group 2 in which the mathematical modelling method is applied are more successful in the post-test when the post-test scores are examined.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, the lack of teachers' knowledge about the mathematical modelling method and their lack of experience in new teaching approaches leads them to not use this method in class (Zeytun et al, 2017). However, this model should be part of mathematics' education.…”
mentioning
confidence: 99%
“…Burkhardt and Pollak (2006), considering mathematical modeling as an element of school curricula, show that modeling makes a significant contribution to the mathematical literacy of future citizens and professionals. The problems of modeling are also discussed by Lester and Kehle (2003), Lesh and Doerr (2003), Lingefjard (2006), Zeytun, Cetinkaya and Erbas (2017). Blomhoj and Hoff Kjeldsen (2006) describe the experiment on conducting a series of seminars on the creation of projects in the field of mathematical modeling in the upper grades of the gymnasium.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…The curriculum of these courses and their efficiency was studied by Brake & Geiger (2011), Kaiser, Schwarz & Buchholtz (2011), Zeytun, Cetinkaya & Erbas (2017. Modeling courses stimulate students' interest in mathematics, develop creativity, communication skills and solving practical problems (Carlson, Larsen & Lesh, 2013).…”
Section: Analysis Of International Studiesmentioning
confidence: 99%